A Historical Perspective on the Future of Innovation in Social Work. (March 2017) - Okpych, Nathanael J.
Changing social work from a profession with innovators to a profession that innovates will likely require an innovation movement. This article draws on lessons from a prior movement in social work to suggest implications for a future innovation movement. Empirical clinical practice (ECP), a movement in social work in the 1970–1990s, sought to transform social work into a profession that was thoroughly grounded in the empirical investigation. The success of ECP was stifled by four factors around investment from key stakeholders, developing useable and effective technologies, propagating the movement, and addressing workplace barriers. This article argues that an innovation movement will require early investment from many sectors and levels of the profession, effective arrangements for generating new options for addressing social problems, effective methods for diffusing and implementing the movement, and frank appraisal of organizational contexts that can stymie innovation.